2021
DOI: 10.3390/su13179695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Compost and Biochar to Mitigate Chlorpyrifos Pollution in Soil and Their Effect on Soil Enzyme Dynamics

Abstract: The widespread environmental contamination of chlorpyrifos (CP) has raised human health concerns and necessitated cost-effective methods for its remediation. The current study evaluated the degradation behavior of CP in compost and biochar amended and unamended (original and sterilized) soils in an incubation trial. Two levels of CP (100 and 200 mg kg−1), compost and biochar (0.50%) were applied, and soil was collected at different time intervals. At the higher CP level (200 mg kg−1), CP a showed lower degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Song [ 6 ] suggested that the key factors leading to increased soil enzyme activity are improvements in the physical structure of the soil and the nutrients and other compounds contained in the biochar. Subsequently, Aziz et al [ 13 ] proposed that fertilizers provide a large amount of unstable carbon to the soil, which microorganisms can use as a substrate food source, thereby increasing dehydrogenase activity and degradation capacity. The adsorption of biochar facilitates enzymatic reactions, as confirmed by Amoakwah et al in a field trial of biochar-amended sandy loam soils, where the application of biochar (30 t·ha −1 ) significantly increased soil urease activity by 1.5 times and dehydrogenase activity by 3.2 times.…”
Section: Introductionmentioning
confidence: 99%
“…Song [ 6 ] suggested that the key factors leading to increased soil enzyme activity are improvements in the physical structure of the soil and the nutrients and other compounds contained in the biochar. Subsequently, Aziz et al [ 13 ] proposed that fertilizers provide a large amount of unstable carbon to the soil, which microorganisms can use as a substrate food source, thereby increasing dehydrogenase activity and degradation capacity. The adsorption of biochar facilitates enzymatic reactions, as confirmed by Amoakwah et al in a field trial of biochar-amended sandy loam soils, where the application of biochar (30 t·ha −1 ) significantly increased soil urease activity by 1.5 times and dehydrogenase activity by 3.2 times.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) analyses were performed on PANalytical diffractometer, using Cu Ka radiation, under a voltage of 40 kV and a current of 200 mA. The Brunauer-Emmett-Teller (BET) specific surface areas of both GO and GO-COOH was analyzed using ASAP 2460 instrument with 77 k via nitrogen adsorption desorption isotherm using a method [ 38 ]. The morphologies were characterized by HITACHI S-3500N scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Decline in the phosphatase activity could be due to inhibitory effect of chlorpyrifos or its metabolites directly on phosphatase enzyme (Das and Mukherjee 1999). According to Aziz et al (2021), amended and unamended chlorpyrifos contaminated treatments showed decreased phosphatase activity up to 15th day and thereafter it stabilized and slowly increased at the end of incubation. Signi cant recovery of enzymatic activities might be due to removal of chlorpyrifos through degradation (Valle et al 2006).…”
Section: Effect Of Treatments On Chlorpyrifos Degradationmentioning
confidence: 99%